KARAKTERISTIK NUGGET IKAN JEBONG (ABALISTESSTELLARIS) DENGAN FORMULASI LABU KUNING (CURCUBITA MOSCHATA) SEBAGAI BAHAN PENGKAT - Mauludiantika, Uni (Fakultas Pertanian Universitas Tanjungpura, 2019)
Nugget is a processed product that is mostly made from chicken meat. One of the alternative of chicken meat substitutes in processing nuggets is minced fish. Triggerfish can be used as the raw material for the making of nugget. Tapioca flour is needed as binder in the process of nugget making. Tapioca flour can be formulated with other ingredients such as pumpkin. The purpose of this study was to find the best formulation between tapioca flour and pumpkin to produce triggerfish nugget that can be accepted by consumers. The results showed that the treatment with the addition of pumpkin significantly affected the water content, carbohydrate content, taste, texture and flavor. The best treatment based on the effectiveness index test is 50 g of pumpkin and 200 g of tapioca flour. The physicochemical properties of triggerfish nuggets have an average water content 47,30%, ash 1,98%, protein 9,28%, fat content 13,39% and carbohydrate content 28,04%. The sensory properties were taste 5,16 (like), texture 5,24 (like), flavor 5,00 (like).Keyword: binder, formulation, triggerfish, pumpkin, nugget